(untitled) (Journal of Nepalgunj Medical College, 2022)
Introduction: COVID-19 is a new infectious disease for which there is currently no treatment and has become a new threat for the populations. Therefore, it is necessary to explore biomarkers to determine disease severity which may help to identify patient at risk of prolonged intensive care or death. Aims: To evaluate the ability of C-reactive protein to predict the severity of COVID-19 infection. Methods: This study was conducted on 83 patients with COVID-19 admitted at COVID Unit of Nepalgunj Medical College Teaching Hospital, Kohalpur from April 2021 to June 2021. COVID-19 infection was diagnosed by Reverse Transcription Polymerase Chain Reaction of nasopharyngeal or throat Swab. The study population was divided into mild, moderate and severe cases. The data on demographic characteristics, clinical features and laboratory findings were collected and analyzed using SPSS version 26. P value less than 0.05 was taken as significant. Results: The mean levels of C-reactive protein in mild, moderate and severe cases were 2.75 mg/L, 9.87 mg/L and 84.48 mg/L respectively (P value = 0.003). This shows that CRP levels were significantly higher in severe cases and could be used as important biomarker to predict the severity of disease in COVID-19. Conclusion: The serum level of C-reactive protein can predict the severity and progression of disease in patient with COVID-19. Thus, C-reactive protein should be used as a prognostic marker in COVID-19.